Suitability of Content in Textbook “English for Nusantara” for Junior High School - Na'imatul Husni (Global Expert: Jurnal Bahasa dan Sastra, 2025)
This research focuses on the analysis of textbooks intended for 9th-grade junior high school students, which are specifically designed according to the latest curriculum known as the Merdeka curriculum. The purpose of this study is to determine the suitability of the textbook content for 8th-grade students based on Thomlinson's theory. The main data source for this study is the English textbook "English for Nusantara SMP/MTS Grade IX”, published by the Ministry of Education, Culture, and Research in 2022. Using a descriptive approach and document analysis, this study focuses on the content of the textbook, examining elements such as impact, learner comfort, building confidence, relevance, language exposure, and more. The textbook's content was examined during data collection, and the analysis included subjective and objective evaluations based on Tomlinson's sixteen criteria for successful learning materials. The textbook mostly complied with Tomlinson's criteria, as evidenced by fifteen of the sixteen criteria being satisfied, such as engaging content, learner participation, and a variety of learning options. However, the textbook lacks facilitation of materials and exercises that can make students' left and right brains work in balance. Keywords: Textbook, Thomlinson’s Theory